Ekonomické a finanční dopady pandemie COVID-19 v konkrétním podniku - Kolářová, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Tato bakalářská práce se zaměřuje na zhodnocení finanční situace firmy DEAS, spol. s r.o. za období 2018-2023 s následným navrhnutím opatření, které vedou ke zlepšení situace. V první části je pomocí odborné literatury popsána teorie, která je potřeba k tématu bakalářské práce. Druhá část je zaměřena na výpočet ukazatelů, které jsou popsány v teoretické části. Vypočtené hodnoty slouží k provedení finanční analýzy firmy. V poslední části jsou uvedeny návrhy, které vedou ke zlepšení finanční situace.

This bachelor thesis is based on the evaluation of the financial situation of DEAS, spol. s.r.o. for the period 2018-2023 with the subsequent proposal of measures that lead to an improvement of the situation. In the first part, the theory that is needed for the topic of the bachelor's thesis is described with the help of specialist literature. The second part is focused on the calculation of indicators, which are described in the theoretical part. The calculated values are used to perform a financial analysis of the company. In the last part, there are proposals that lead to an improvement of the financial situation.
Economic and financial impacts of the COVID-19 pandemic in a specific company
Keywords: Finanční analýza; COVID-19; rozvaha; výkaz zisků a ztrát; SWOT analýza; spider analýza; poměrové ukazatele; likvidita; rentabilita; Financial analysis; COVID-19; balance sheet; profit and loss statement; SWOT analysis; spider analysis; ratio indexes; liquidity; profitability